Implementation of MCDM model in lean manufacturing using grey relational analysis in automotive industry - K, Venkataraman; V. Sivaramakrishnan, T; Murugan, N; Deepankar, D; Srinivasa Raghavan, B (International Journal of Engineering and Technology, 2018)
The present economic situation shows the consistent demand for profitable solutions that allow business organizations to gain better ad-vantage. Due to this reason, many organizations search for methodologies that allow them to improve their products and services improve their processes, reduce costs, and improve the profit and customer satisfaction. This has been implemented through lean techniques in their managerial and production methods. As we know Lean production system mainly emphasizes on the waste elimination, using simple and visual techniques. This paper is an attempt to optimize process layout and waste expulsion for automotive powertrain in a leading automo-tive company by using lean manufacturing techniques. In this paper, the existing process in place for machining of cam shaft is analysed and process layout is optimized to reduce cycle time and lead time. In order to reduce the cycle time, the process parameters such a speed, feed and depth of cut are optimized for increased material removal rate (MRR) and decreased surface roughness (RA) by using Grey Relational Analysis (GRA) technique. As MRR is inversely related to cycle time, optimization of parameters for higher MRR reduces the cycle time. Grey Relational Analysis is done by using Design Xpert software.Â Â